(untitled) (New York, 2000)
This anthology covers writers and works of English literature. Among the major works included are the complete texts of Milton's "Paradise Lost" and Mary Shelley's "Frankenstein"; Shakespeare's "Twelfth Night"; Beckett's tragicomic "Endgame"; and Achebe's "Things Fall Apart". The 7th edition features works by 60 women writers, 21 writers new to the "Norton Anthology", 20 represented with additional selections or reselected works. Fourteen new and expanded thematic clusters gather short texts that illuminate cultural, historical, and literary concerns within each period. Examining 20th-century literature in English, this edition reflects the global reach of literature in English with ten new authors - Jean Rhys, Chinua Achebe, Alice Munro, V. S. Naipaul, Anita Desai, Les Murray, Salman Rushdie, J. M. Coetzee, Eavan Boland, and Paul Muldoon. "The Persistence of English", a new essay by Geoffrey Nunberg, Stanford University and Xerox Palo Alto Research Center, provides a lively exploration of the English language - its emergence and spread, and its apparent "triumph" as a world language. Visual materials are included from several periods - Hogarth's satiric "Marriage A-la-Mode", engravings by Blake, and illustrations by Dante Gabriel Rossetti. Period introductions, author headnotes, annotations, and bibliographies have been thoroughly revised, many completely rewritten, for the 7th Edition. New pedagogical features include timelines for each period and revised endpaper maps.
Văn học trong giảng dạy ngôn ngữ Anh
Keywords: English literature,Great Britain,Văn học Anh,Vương quốc Anh; Literary collections,Bộ sưu tập văn học